Understanding Quaternary paleoclimatic shifts and their impact on hominin settlement in the lower Soan Valley, sub-Himalayas - Nadir Fawad; Zhongbo Wang; Daidu Fan; Christopher J. Bae; Muhammad Kamran (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Baseline Assessment of Municipal Wastewater Parameters in 20 Rural Areas of Punjab, Pakistan: A First-Ever Framework for Development of Sustainable Decentralized Treatment Plants - Abdul Manan; Tausif Ahmad; Syed Nadir Hussain; Hafiz Muhammad Anwaar Asghar (Water, Air, & Soil Pollution, 2026)

Unraveling Luteolin’s Modulatory Effects on α-Synuclein Aggregation: A Combined Biophysical, Computational, and C. elegans Approach - Syed Moasfar Ali; Md Nadir Hassan; Nida Zaidi; Muhammad Uzair Ashraf; Mahmood Akbar; Aamir Nazir; Rizwan Hasan Khan (Cell Biochemistry and Biophysics, 2026)

Pathways to sustainable development: an examination of innovation and institutional quality’s role in green GDP Outcomes Using QCA - Muhammad Nadir Shabbir; Kainat Iftikhar; Mirza Muhammad Naseer (Environment, Development and Sustainability, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Climate smart agriculture: A path to sustainable farming in China - Duong Thuy Linh; Muhammad Nadir Shabbir (Food and Humanity, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

New paradigms to evaluate the stratigraphy for the geological and geoarchaeological prospects of the upper and post-Siwaliks in the Soan Valley, Upper Indus Basin, Pakistan - Nadir Fawad; Daidu Fan; Taixun Liu; Anne Dambricourt Malassé; Muhammad Kamran; Qazi Adnan Ahmed; Fahad Ali (Quaternary International, 2025)

Advancing algae-based Bioenergy: Techno-Economic assessment of hydrogen and biochar production from algal biomass - Aliyan Tanweer; Syed Ali Ammar Taqvi; Bilal Kazmi; Safiya Khatoon; Muhammad Taha; Muhammad Nadir; Farooq Ahmad; Naveed Ahmad (Biomass and Bioenergy, 2025)

Foliar Application of Silicon Alleviates Drought Stress in Chickpea (Cicer arietinum L.) by Improving Growth, Photosynthetic and Antioxidant Metabolism - Muhammad Faizan Ali; Mukhtar Ahmed; Laiba Mukhtar; Nadir Ali; Ghulam Qadir; Rifat Hayat; Shakeel Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Sublethal effect and molecular responses of Musca domestica to cinnamon extracts - Akram Alghamdi; Muhammad Nadir Naqqash; Nimra Batool; Muhammad Asif Farooq; Ahmed Noureldeen; Hadeer Darwish; Attalla F. El-kott; Salama A. Salama; Yasser Rabea Elmarassi (The Science of Nature, 2025)

Impact of field evolved resistance on biological parameters of non-targeted Aedes aegypti populations - Nimra Batool; Muhammad Asif Farooq; Waqar Jaleel; Ahmed Noureldeen; Akram Alghamdi; Hadeer Darwish; Naif H. Ashri; Muhammad Nadir Naqqash (Ecotoxicology, 2025)

Environmental Heavy Metal Exposure and Associated Cardiovascular Diseases in Light of the Triglyceride Glucose Index - Muhammad Bilal Sardar; Mohsin Raza; Ammara Fayyaz; Muhammad Asfandyar Nadir; Zain Ali Nadeem; Muhammad Babar (Cardiovascular Toxicology, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Heterologous expression of distinct insecticidal genes in potato cultivars encodes resistance against potato tuber moth, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae) - Muhammad Salim; Allah Bakhsh; Muhammad Nadir Naqqash; Ayhan Gökçe (Journal of Plant Diseases and Protection, 2024)
The potato tuber moth, Phthorimaea operculella (Zeller), is a notorious insect pest of potato incurring substantial yield losses in the field as well as in storage. Chemical control is difficult to exercise due to the latent feeding of the caterpillars and their ability to develop resistance against insecticides. One of the essential components of efficient insect-resistant management is using two or more different insecticidal genes in transgenic crops to effectively avoid and delay the resistance development in insect pests. Two constructs, namely DS-1 ( cry3A + SN-19 genes) and DS-2 ( OCII + SN-19 genes) in pCAMBIA1301 binary vector, were developed and were transformed in potato cultivars (Agria and Lady Olympia) via Agrobacterium -mediated transformation. The molecular analysis confirmed gene integration and expression of the introduced genes in transgenic plants. The insecticidal effects of incorporated genes in transgenic plants were assessed against 1st, 2nd, 3rd, and 4th instar potato tuber moth (PTM) larvae. The transgenic plants endured significantly high mortalities (100%) of larval stages of PTM within 72 h. Our results show that these transgenic potato plants have the potential to control populations of PTM and are also useful tools in managing PTM that would ultimately reduce the dependency on conventional chemical pesticides with potentially less or minimal hazards. These lines can also serve as an excellent source of germplasm for potato breeding program.

Computational analysis of fluid dynamics in open channel with the vegetated spur dike - Sohail Iqbal; Muhammad Siddique; Ali Hamza; Nadir Murtaza; Ghufran Ahmed Pasha (Innovative Infrastructure Solutions, 2024)

Corrigendum to “Could soil microplastic pollution exacerbate climate change? A meta-analysis of greenhouse gas emissions and global warming potential” [Environ. Res. 252 (2024) 118945/ ER-23-14694R1] - Shahid Iqbal; Jianchu Xu; Muhammad Saleem Arif; Awais Shakoor; Fiona R. Worthy; Heng Gui; Sehroon Khan; Dengpan Bu; Sadia Nadir; Sailesh Ranjitkar (Environmental Research, 2024)

Heterologous expression of bacterial dehydrin gene in Arabidopsis thaliana promotes abiotic stress tolerance - Nadir Zaman Khan; Akhtar Ali; Waqar Ali; Muhammad Aasim; Tariq Khan; Zaryab Khan; Iqbal Munir (Physiology and Molecular Biology of Plants, 2023)

Impact of green human resource management on green creativity in pharmaceutical companies: mediation role of green mindset - Muhammad Haseeb Shakil; Rana Nadir Idrees; Sadaf Ehsan; Waseem Anwar (Environmental Science and Pollution Research, 2023)

Demographic features and population projection of resistant and susceptible populations of Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - Muhammad Nadir Naqqash; Ayhan Gökçe; Allah Bakhsh; Muhammad Salim (Phytoparasitica, 2023)

Iron-doped zinc oxide nanoparticles-triggered elicitation of important phenolic compounds in cell cultures of Fagonia indica - Atta Ullah Khan; Tariq Khan; Mubarak Ali Khan; Akhtar Nadhman; Muhammad Aasim; Nadir Zaman Khan; Waqar Ali; Nausheen Nazir; Muhammad Zahoor (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

GC-MS & preliminary screening profile of Cordia sinensis leaves – antiglycation, antifungal and insecticidal agents - Kehkashan Khan; Munawwer Rasheed; Muhammad Nadir; Sadiqa Firdous; Shaheen Faizi (Natural Product Research, 2021)

Phytochemical and pharmacological profile with biogenetic correlation of bioactive phytoconstituents from the stems of Cordia sinensis Lam - Kehkashan Khan; Munawwer Rasheed; Muhammad Nadir; Sadiqa Firdous; Shaheen Faizi (Natural Product Research, 2021)

Exploring socio-hydrological determinants of crop yield in under-performing irrigation schemes: pathways for sustainable intensification - Muhammad Khalifa; Nadir Ahmed Elagib; Bashir Mohammed Ahmed; Lars Ribbe; Karl Schneider (Hydrological Sciences Journal, 2020)

Biochar increased photosynthetic and accessory pigments in tomato (Solanum lycopersicum L.) plants by reducing cadmium concentration under various irrigation waters - Muhammad Abid; Subhan Danish; Muhammad Zafar-ul-Hye; Muhammad Shaaban; Muhammad Mutahir Iqbal; Abdur Rehim; Muhammad Farooq Qayyum; Muhammad Nadir Naqqash (Environmental Science and Pollution Research, 2017)

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families - Naveed Wasif; Syed Kamran ul-Hassan Naqvi; Sulman Basit; Nadir Ali; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2011)